NILAI-NILAI MORAL DALAM DONGENG PUTRI BERKULIT KUNING KARYA MADE TARO - Ni Luh Ayu Catri; Ketut Yarsama (Widyadari, 2024)
Fairy tales are fun for children, and can optimize children's character development in achieving thinking development. Intellectual intelligence can be fulfilled if parents are able to take the time to tell stories to their children. This research discusses the moral values contained in the fairy tale "The Yellow-Skinned Girl" by Made Taro. In analyzing using the Moral Education theory according to Sjarkawi, Moral education is an educational process that aims to foster the formation of good morals for everyone and can change a person's behavior to become moral. In this research, repeated reading and note-taking techniques were used, focusing on the moral values contained in the fairy tales. Data collection uses library methods, this type of research is descriptive qualitative. The method for presenting data analysis uses an informal method. As a result of the discussion, there are eight moral message quotes that the author can analyze. Among them, a wife's loyalty to her husband, not being able to distinguish between daughters and sons, a mother's struggle to save her child, not distinguishing between daughters and sons, a mother's struggle to save her child, not being allowed to speak lies, a children who diligently help their parents, children's love for their biological father.